2023
DOI: 10.1007/s12035-023-03359-y
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes (T2DM) and Parkinson’s Disease (PD): a Mechanistic Approach

Abstract: Growing evidence suggest that there is a connection between Parkinson’s disease (PD) and insulin dysregulation in the brain, whilst the connection between PD and type 2 diabetes mellitus (T2DM) is still up for debate. Insulin is widely recognised to play a crucial role in neuronal survival and brain function; any changes in insulin metabolism and signalling in the central nervous system (CNS) can lead to the development of various brain disorders. There is accumulating evidence linking T2DM to PD and other neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 244 publications
(216 reference statements)
0
2
0
Order By: Relevance
“…While there is mounting evidence linkingT2DM with PD [ 41 , 42 ], and suggesting antidiabetic agents as a novel treatment for PD [ 5 ], less is known about the association between PD and T1DM. For PD, the changes in brain insulin resistance (BIR) and α-synuclein protein at synapses, as well as the dopaminergic loss in specific brain regions, eventually yield to the manifestation of the classic motor symptoms corresponding to the typical PD phenotype [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there is mounting evidence linkingT2DM with PD [ 41 , 42 ], and suggesting antidiabetic agents as a novel treatment for PD [ 5 ], less is known about the association between PD and T1DM. For PD, the changes in brain insulin resistance (BIR) and α-synuclein protein at synapses, as well as the dopaminergic loss in specific brain regions, eventually yield to the manifestation of the classic motor symptoms corresponding to the typical PD phenotype [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell survival effects of the PI3K-AKT signalling pathway are promoted by (a) inhibiting excessive apoptosis and (b) attenuating the pro-inflammatory NF.κB-dependent signalling pathways, (c) attenuating FOXO1-mediated MT oxidative stress, (d) reducing α-syn aggregation by preventing the GSK3β inhibition of IDEs that break down the α-syn protein, and (e) promoting synapse regeneration by mTORC1/2 activation [1,233,234]. All four signalling pathways support neuronal growth and survival [2,192,[235][236][237].…”
Section: Insulin Resistancementioning
confidence: 99%
“…In PD, the high metabolic rate of brain dopaminergic neurons increases their vulnerability to the combined detrimental effects of increased MT oxidant stress and the MT accumulation of toxic α-synO. Brain IR further compounds the damaging impact of MT oxidant stress and toxic α-synO forms [2,28,235,237]. Insulin signalling supports normal MT biogenesis (i.e., oxidative function) via the modulation of the mTORC and FOXO1 signalling pathways, which converge and adjust the activity of peroxisome proliferatoractivated receptor-γ coactivator 1-α (PGC1α).…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that patients affected by PD and T2D comorbidity, suffer from more severe motor symptoms and cognitive decline (6)(7)(8)(9). Moreover, it has been suggested that T2D and PD share underlying pathophysiological mechanisms (5,10,11). Along with the dysregulated energy metabolism, aberrant protein aggregation, accumulation of reactive oxygen species and inflammation, insulin resistance seems to play a pivotal role in converging most of these common mechanisms.…”
Section: Introductionmentioning
confidence: 99%